(N|LEKTRONIKA SLOEW (BSiOb2 (NNA KREMNII (B/s - (NbARABAN(B, (NaLEKSANDR pETROWI^s; (NbULAWINOW(B, (NwLADIMIR wLADIMIROWI^s; (NkONOROW(B, (NpAWEL pAWLOWI^s ((NlENINGRAD (B:s (Nlgu(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 275-301 (640 (NNAZW(B.)s
(Nlgus
Keywords: (NkREMNIJ(B, (NDWUOKISXs -- (NpOWERHNOSTNYE SWOJSTWAs